Physical and microbial properties of fruit flavoured fermented cowmilk and soy milk (yoghurt-like) under different temperature of storage - E.O., Farinde; V.A., Obatolu; M.A., Oyarekua; H. A, Adeniran; S. I., Ejoh; O.T., Olanipekun (Global Journal of Food and Agribusiness Management, 2011)
Quest for affordable shelf stable and acceptable fermented milk from non- dairy source informed this study, in which soymilk and dairy milk were processed into fermented drink (yoghurt-like). Water from fermented maize (maize steep water) was used as starter source while natural extracts of orange , pineapple, grape and banana were employed as flavors. The flavored fermented milk samples were physically observed and microbiologically evaluated for 17 days. Samples stored at ambient lasted for 24 hours. Change in color and flavor were observed by Day 2 and Day 4 at ambient (± 270C) and refrigerated temperature (±4OC ) respectively. Total aerobic count and Lactic acid bacteria count of most of the samples increased by Day 4 at refrigerated temperature followed by a decrease from Day 10. Staphylococcus count was nil at freezing temperature in all the fermented milk samples. Freezing drastically reduce the microbial load of all the fermented milk (yoghurt-like) samples